Feeding tadpoles cloned from Rana erythrocyte nuclei. - DiBerardino, M A (1986)
Diploid frog nuclei from differentiated somatic cells, transplanted into enucleated eggs to determine whether cell specialization generally involves irreversible genetic changes, have shown that nuclei from specialized somatic cells still contain the genes specifying the cell types and organ systems of swimming tadpoles. However, those tadpoles failed to feed and did not survive beyond the initial tadpole stages. Here we report that, after incubation in oocytes, triploid erythrocyte nuclei from juvenile frogs of Rana pipiens directed the formation of feeding tadpoles that survived up to a month and had differentiated hind limb buds. These tadpoles occurred at a high yield and showed the most extensive development so far obtained from documented differentiated somatic nuclei.